Imaginaires miniers et conflits sociaux en Bolivie : une approche multiniveaux du conflit de Mallku Khota - Claude Le Gouill (Cahiers des Amériques Latines)
Since the election of Evo Morales, Bolivia has experienced a contradiction between environmental discourse around the indigenous imaginary and extractive practices. These contradictions are not unique to the government but also affect many social organizations. The subject of mining is particularly revealing of these tensions. From the case of the Northern region of Potosí and the Mallku Khota conflict, we will show that these conflicts are not only based on a multiplication of actors and on competing development projects, but also on both a material reality and a discursive, normative and symbolic repertoire leading to a redefinition of natural resources management. Through a multi-level approach we analyze the flow of imaginaries and the mobilization of resources that the different actors use in a strategic ways. We will therefore see how the discourses of “acceptance” or “rejection” of mining depend less on the ideological environmental discourse than on the construction of coalitions and the development of the conflict.